2019
DOI: 10.1111/cxo.12817
|View full text |Cite
|
Sign up to set email alerts
|

Contrast sensitivity of amblyopic eyes in children with myopic anisometropia

Abstract: CSF at the middle and higher frequencies was reduced in the amblyopic eyes associated with myopic anisometropia compared to the fellow eyes of the same amblyopic children as well as to eyes of control subjects with high myopia but no amblyopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Previously, we reported that patients with amblyopia associated with myopic anisometropia had significantly reduced contrast sensitivity at the middle and higher spatial frequencies. 10 Although a contrast sensitivity function test measures an individual's contrast sensitivity thoroughly, it is a long procedure which may present some obstacles in routine clinical application. The automated ETDRS-CT test, which requires minimum effort from the participants and less clinical testing time may have a broader application in both clinical care and experimental trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported that patients with amblyopia associated with myopic anisometropia had significantly reduced contrast sensitivity at the middle and higher spatial frequencies. 10 Although a contrast sensitivity function test measures an individual's contrast sensitivity thoroughly, it is a long procedure which may present some obstacles in routine clinical application. The automated ETDRS-CT test, which requires minimum effort from the participants and less clinical testing time may have a broader application in both clinical care and experimental trials.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that patients with amblyopia associated with myopic anisometropia had significantly reduced contrast sensitivity at the middle and higher spatial frequencies 10 . Although a contrast sensitivity function test measures an individual’s contrast sensitivity thoroughly, it is a long procedure which may present some obstacles in routine clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Myopia was defined as ≥-1.00 D in the cycloplegic spherical equivalent. Myopic anisometropia was defined as myopia in both eyes and an interocular difference of ≥3.00 D in the cycloplegic spherical equivalent (7,8). An eye with a BCVA of ≤20/30 or at least 2 Snellen visual acuity lines of difference in the fellow eye was considered amblyopic (7,8).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have reported that amblyopia and anisometropia were associated with developmental abnormalities of the visual system, including the visual cortex, lateral geniculate nucleus, retina, retinal nerve fiber layer, optic nerve, macula, axial length, and the cornea (4)(5)(6)(7)(8). The relationship between the pupil and amblyopia has been examined.…”
Section: Introductionmentioning
confidence: 99%
“…CS refers to the ability to detect a difference in brightness (or luminance) between adjacent objects or areas in a space. CS may be abnormal in amblyopia, optic neuritis, cataract, and glaucoma, but also decreases in the presence of photophobia [ 4 , 5 ]. Lew et al [ 6 ] reported that photophobia in IXT was associated with a distant exodeviation greater than 25 prism diopters (PD) and stereoacuity worse than 60 arcsec, but no analysis was performed with CS measurement.…”
mentioning
confidence: 99%